A 3‐week multimodal intervention involving high‐intensity interval training in female cancer survivors: a randomized controlled trial. Issue 3 (11th February 2016) - Schmitt, Joachim; Lindner, Nathalie; Reuss‐Borst, Monika; Holmberg, Hans‐Christer; Sperlich, Billy
Abstract: To compare the effects of a 3‐week multimodal rehabilitation involving supervised high‐intensity interval training (HIIT) on female breast cancer survivors with respect to key variables of aerobic fitness, body composition, energy expenditure, cancer‐related fatigue, and quality of life to those of a standard multimodal rehabilitation program. A randomized controlled trial design was administered. Twenty‐eight women, who had been treated for cancer were randomly assigned to either a group performing exercise of low‐to‐moderate intensity (LMIE; n = 14) or a group performing high‐intensity interval training (HIIT; n = 14) as part of a 3‐week multimodal rehabilitation program. No adverse events related to the exercise were reported. Work economy improved following both HIIT and LMIE, with improved peak oxygen uptake following LMIE. HIIT reduced mean total body fat mass with no change in body mass, muscle or fat‐free mass (best P < 0.06). LMIE increased muscle and total fat‐free body mass. Total energy expenditure ( P = 0.45) did not change between the groups, whereas both improved quality of life to a similar high extent and lessened cancer‐related fatigue. This randomized controlled study demonstrates that HIIT can be performed by female cancer survivors without adverse health effects. Here, HIIT and LMIE both improved work economy, quality of life and cancer‐related fatigue, body composition or energy expenditure. Since the outcomes were similar, but HIIT takes less time, this may be a time‐efficient strategy for improving certain aspects of the health of female cancer survivors. Abstract : The effects of a 3‐week multimodal rehabilitation involving supervised high‐intensity interval training (HIIT) on female breast cancer survivors with respect to key variables of aerobic fitness, body composition, energy expenditure, cancer‐related fatigue and quality of life were compared to those of a standard multimodal rehabilitation program. Since the outcomes were similar, but HIIT takes less time, this may be a time‐efficient strategy for improving certain aspects of the health of female cancer survivors.